Adjusting D-dimer to Lung Disease Extent to Exclude Pulmonary Embolism in COVID-19 Patients (Co-LEAD) - Planquette, Benjamin; Khider, Lina; Berre, Alice Le; Soudet, Simon; Pernod, Gilles; Mao, Raphaël Le; Besutti, Matthieu; Gendron, Nicolas; Yanoutsos, Alexandra; Smadja, David M.; Goudot, Guillaume; Kahf, Salma Al; et al. (Thrombosis and haemostasis, 2022)
Abstract Objective D-dimer measurement is a safe tool to exclude pulmonary embolism (PE), but its specificity decreases in coronavirus disease 2019 (COVID-19) patients. Our aim was to derive a new algorithm with a specific D-dimer threshold for COVID-19 patients. Methods We conducted a French multicenter, retrospective cohort study among 774 COVID-19 patients with suspected PE. D-dimer threshold adjusted to extent of lung damage found on computed tomography (CT) was derived in a patient set ( n = 337), and its safety assessed in an independent validation set ( n = 337). Results According to receiver operating characteristic curves, in the derivation set, D-dimer safely excluded PE, with one false negative, when using a 900 ng/mL threshold when lung damage extent was <50% and 1,700 ng/mL when lung damage extent was ≥50%. In the derivation set, the algorithm sensitivity was 98.2% (95% confidence interval [CI]: 94.7–100.0) and its specificity 28.4% (95% CI: 24.1–32.3). The negative likelihood ratio (NLR) was 0.06 (95% CI: 0.01–0.44) and the area under the curve (AUC) was 0.63 (95% CI: 0.60–0.67). In the validation set, sensitivity and specificity were 96.7% (95% CI: 88.7–99.6) and 39.2% (95% CI: 32.2–46.1), respectively. The NLR was 0.08 (95% CI; 0.02–0.33), and the AUC did not differ from that of the derivation set (0.68, 95% CI: 0.64–0.72, p = 0.097). Using the Co-LEAD algorithm, 76 among 250 (30.4%) COVID-19 patients with suspected PE could have been managed without CT pulmonary angiography (CTPA) and 88 patients would have required two CTs. Conclusion The Co-LEAD algorithm could safely exclude PE, and could reduce the use of CTPA in COVID-19 patients. Further prospective studies need to validate this strategy.